Etika Administrasi Kepegawaian dan Peningkatan Kualitas Pelayanan Publik: Analisis Profesionalisme ASN pada Dinas ESDM Provinsi Kalimantan Tengah - Griselda Okta Viani; Helsa Aprilia H Mamud; Tiara Tiara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the interrelationship between the implementation of administrative ethics in civil service, the professionalism of State Civil Apparatus (ASN), and the quality of public service delivery at the Provincial Department of Energy and Mineral Resources of Central Kalimantan, employing a qualitative case study approach. Through in-depth interviews, structured observations, and document analysis, the research finds that integrity, transparency, and ethical accountability function not merely as moral norms but as structural foundations that reinforce ASN professionalism in performing service functions, particularly within licensing processes that demand administrative certainty and responsiveness. Empirical findings indicate that professionalism—reflected in technical competence, procedural discipline, and ethical commitment—acts as a catalyst linking ethical values to effective and adaptive public service performance. Nevertheless, the study also identifies structural and cultural impediments, including regulatory inconsistencies, fragmented coordination, and limited training opportunities, all of which hinder the internalization of ethical principles and professional practice within the bureaucracy. Theoretically, the study posits that harmonizing administrative ethics and professionalism is a prerequisite for achieving key indicators of good governance, such as responsiveness, service effectiveness, and institutional accountability. Practically, the study recommends strengthening ethics training, enhancing ASN professional capacity, and advancing managerial reforms grounded in modern governance as strategic efforts to sustainably improve public service quality.